Pancasila and Communism: An Ideological Comparison - Duha, Adam Maulidin (Indonesian Journal of Pancasila and Global Constitutionalism, 2022)
Research in this journal discusses the ideologies that exist in the world and compares and looks for differences with the ideology of Pancasila. The research method used is descriptive analysis which discusses the differences between the ideology of Pancasila and the ideology of communism. In the Pancasila ideology, it is true that the attitudes and characteristics of the humble and flexible Pancasila ideology have contained all existing values ​​and have other ideologies. While the ideology of communism according to Karl Max is so easy to use as a tool of the rulers to realize their desires, either by coercion or using radical methods. Of course, the two ideologies are very inversely proportional, so the Indonesian people establish the ideology of Pancasila by instilling noble values ​​and openness to realize the ideals of the Indonesian State.